1991
DOI: 10.1105/tpc.3.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a higher plant psbA gene in Synechocystis 6803 yields a functional hybrid photosystem II reaction center complex.

Abstract: The psbA gene codes for the D1 polypeptide of the photosystem I 1 reaction center complex and is found in a11 photosynthetic organisms that carry out oxygenic photosynthesis. Here we describe the construction and characterization of a strain of the cyanobacterium Synechocystis sp PCC 6803 in which the three endogenous psbA genes are replaced by a single psbA gene from the chloroplast genome of the higher plant Poa annua. The resulting chimeric strain, KWPAS, grows photoautotrophically with a doubling time of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Previously, it was shown that a specific D1 copy (D1:2 form) encoded by the psbA3 gene in Synechococcus elongatus and Thermosynechococcus elongatus is responsible for a temperature downshift of the B and Q bands in TL curves (Sane et al, 2002;Sander et al, 2010;Sugiura et al, 2014). This functional difference is related to the presence of a glutamate residue instead of a glutamine at position 130 in the D1:2 protein sequence, which interacts with a key pheophytin cofactor (Nixon et al, 1991;Rappaport et al, 2002). Contrary to Synechococcus, the psbA3 gene of Synechocystis does not encode this specific D1:2 form, but both the psbA2 and psbA3 genes encode identical D1 proteins (for a review on D1 forms see Mulo et al, 2009;, which do not possess a Q130E mutation.…”
Section: Flv2/flv4 Accelerates Charge Separation Kineticsmentioning
confidence: 99%
“…Previously, it was shown that a specific D1 copy (D1:2 form) encoded by the psbA3 gene in Synechococcus elongatus and Thermosynechococcus elongatus is responsible for a temperature downshift of the B and Q bands in TL curves (Sane et al, 2002;Sander et al, 2010;Sugiura et al, 2014). This functional difference is related to the presence of a glutamate residue instead of a glutamine at position 130 in the D1:2 protein sequence, which interacts with a key pheophytin cofactor (Nixon et al, 1991;Rappaport et al, 2002). Contrary to Synechococcus, the psbA3 gene of Synechocystis does not encode this specific D1:2 form, but both the psbA2 and psbA3 genes encode identical D1 proteins (for a review on D1 forms see Mulo et al, 2009;, which do not possess a Q130E mutation.…”
Section: Flv2/flv4 Accelerates Charge Separation Kineticsmentioning
confidence: 99%
“…The choice of this substitution was suggested by the relative ease of targeting genes into a cyanobacterial genome compared with the nuclear or chloroplast genomes of plants, as required for the reverse combination. Hybrid PSIIs constructed in this way have already been used to study the function of essential components of the core, such as D1 and CP47 polypeptides [15,16].…”
mentioning
confidence: 99%
“…This may suggest that the extension is not important in the binding of the substrate to the processing enzyme. The fact that the psbA gene product of a higher plant is processed by the enzyme in cyano- bacterial cells [16], the D1 precursor protein of which contains largely different C-terminal extension compared to that of higher plants, further supports this interpretation. In order to test this possibility, the inhibitory effect of a polypeptide, corresponding to the Cterminal 9 amino acids (P-9) to the processing activity, using an in vitro translated D1 precursor protein, was examined in the experiment shown in Fig.…”
Section: Resultsmentioning
confidence: 82%